Pengaruh Penggunaan Wizer.me sebagai Media Belajar Mandiri ditinjau dari Hasil Belajar Siswa pada Mata Pelajaran Matematika di SMK Kartika XIX-3 Kota Cirebon - Septiani, Dian Amelia; Darwan, Darwan; Manfaat, Budi (MATHEdunesa, 2024)
In studying mathematics, students are often only provided with makeshift media, such as printed books. Providing such monotonous media can result in students being less interested in learning mathematics and having an impact on the acquisition of unsatisfactory student learning outcomes. In an increasingly advanced digital era, the use of interactive media assisted by wizer.me can be an effective solution to overcome these problems and improve student learning outcomes in mathematics. The purpose of this research is to find out the differences in student learning outcomes using media wizer.me and conventional media, namely printed books in mathematics. In addition, to determine the effect of using wizer.me as an independent learning medium in terms of student learning outcomes in mathematics. The type of research used is quasi-experimental in the form of nonequivalent control group design with a quantitative approach. This research was conducted at Kartika XIX-3 Vocational School, Cirebon City, which consisted of 2 classes, namely X pharmacy as the experimental class and X nursing as the control class. Data collection techniques in this study used test techniques and the instrument used was an objective test to measure student learning outcomes in aspects of cognitive ability. After the objective test data is collected, the processing is carried out by means of statistical analysis. The results showed that: (1) Based on the results of the independent t test, a significance value of 0.007 <0.05 was obtained. So it can be stated that there are differences in student learning outcomes using media wizer.me and conventional media in mathematics. (2) Based on the results of the calculation of the type d effect size, the value of d is 0.90 > 0.80 and is included in the large category. Thus, the use of wizer.me as a self-learning medium has a major positive influence on student learning outcomes in mathematics.